Ethos of Education And Welfare of Muslim Migrants: Case Study in Migrant Settlement of Pangkoh, Pulang Pisau Regency, Central Kalimantan Province - Abdul Qodir (Universitas Ahmad Dahlan, 2012)
AbstractThis study focused on issues of education and welfare ethos, which define: (1) how the ethos phenomenon of Muslim migrants toward education, and (2) how the image of success in educational and welfare ethos in Pangkoh. This research aims to describe and interpret ethos phenomena of education, success, and welfare through perspective of psychology and Islam. Subjects were Muslim migrants living in Pangkoh. They are grouped in two sections of migrants namely migrant with secondary education by 12 families, and those with basic education, primary school or an equivalent amounting 11 families. Data collection techniques using primary techniques of in-depth interviews and observations related to the problem. This study shows Muslim migrant groups who have basic education are not directly educational ethos, but they produce graduates capable of working. Migrant children claimed their success in the struggle of parents are blessed by Allah SWT. The contribution of this research will develop the ethos of the Muslim migrants for valuable input for local governments Pulang Pisau, and as a true imaging.Keywords: Ethos, education, welfare, muslim migrant.Â